Rumen fermentation, urease activity and performance of cattle given palm kernel cake-based diet - Abdullah, N. (Elsevier, 1988)
The rumen pH, ammonia (NH3) and volatile fatty acid (VFA) concentrations and patterns, protozoal population, bacterial urease activity of rumen liquor and tissues along the gastrointestinal tract, and the growth performance were studied in 4 male and 4 female 14-month-old Draughtmaster cattle fed palm kernel cake-based diet ad libitum for 185 days. Palm kernel cake (solvent and expeller types) made up 89% of the diet. The animals showed a satisfactory response to the diet, indicating a high nutritive value of the feed material. The concentration of NH3 was relatively high in all animals, with mean values of 35.5 ± 10.97 and 39.19 ± 11.50 mmol 1-1 for males and females, respectively. The mean VFA concentration for all animals was 78.8 ± 7.9 mmol 1-1. The molar percentages of acetate, propionate, isobutyrate, butyrate, isovalerate and valerate were 52.3 ± 1.6, 26.2 ± 1.9, 5.7 ± 1.0, 10.3 ± 1.8, 4.2 ± 1.0 and 1.4 ± 0.7, respectively. Protozoa were not detected in the rumen liquor of all animals. Urease activity units per ml of liquor were 9.16 ± 1.78 for males and 9.14 ± 2.20 for females, while the mean of 8 tissue sites (each 6.25 cm2) of the reticulo-rumen was slightly higher for males (6.18 ± 2.45) than for females (4.50 ± 2.73). Urease activity was significantly affected (P < 0.05) by tissue sites in the reticulo-rumen with the areas around the caudal pillar showing the highest activity. The other sites of the gastrointestinal tract recorded low to very low urease activities (0.00-1.76 units).